The draft protocol on the creation of the Court of Justice of Mercosur – a new milestone in the judicialization of regional integration law - Kühn, Werner Miguel (Journal of the Belarusian State University. International Relations, 2018)
Several years have passed since Parlasur submitted a draft protocol to the Member States of Mercosur for approval, envisaging the creation of a permanent Court of Justice for this South American integration system. Repeated calls for a reform of Mercosur’s dispute settlement mechanism have remained unheard ever since, as the national governments’ focus of attention has shifted to the economic and political difficulties this regional integration system had to face. The recent election of a new government in Argentina has raised hopes that the reform would be finally implemented. The present article will explain the reasons for the necessity of this reform. It will further provide an account of the key features of the draft protocol, which intends to remedy the shortcomings of the dispute settlement mechanism currently in place, while highlighting the influence European and Latin American integration law has had. The conclusion to be drawn is that the draft protocol constitutes a milestone in the judicialization of regional integration law and that a failure to make it legally binding would have to be considered a missed opportunity for regional economic integration.
Keywords: supranationality; procedural law; dispute settlement mechanisms; comparative law; Mercosur; Andean Community; Central American Integration System; European Union; European Free Trade Association; Eurasian Economic Union